ESG Scores and Financial Growth: A Pathway to Corporate Sustainability - Vongpatchim, Parichat; Chainirun, Pisek (International Journal of Economics and Financial Issues, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) scores and financial performance within publicly listed companies in Thailand. Data from 2019 to 2024, spanning multiple industries, were analyzed. The findings reveal a significant positive correlation between ESG scores and financial performance metrics. Companies with higher ESG scores exhibited superior Return on Equity (ROE), Return on Assets (ROA), and increased market valuations. The study also highlights that the impact of ESG varies across industries. The energy and manufacturing sectors experienced pronounced positive effects from environmental practices, while governance initiatives drove financial performance in the financial and technology sectors. In the agricultural sector, environmental strategies such as sustainable farming and eco-friendly tourism played a pivotal role in enhancing financial resilience. These findings underscore the importance of integrating ESG principles into corporate strategies to gain competitive advantages, strengthen investor confidence, and achieve sustainable growth. The insights from this research provide valuable guidelines for policymaking, investment decisions, and organizational management in the Thai context.